Heterogeneity of coronary heart disease risk factors in Indian, Pakistani, Bangladeshi, and European origin populations: cross sectional study. Issue 7204 (24th July 1999) - Bhopal, Raj; Unwin, Nigel; White, Martin; Yallop, Julie; Walker, Louise; Alberti, K G M M; Harland, Jane; Patel, Sheila; Ahmad, Naseer; Turner, Catherine; Watson, Bill; Kaur, Dalvir; et al.
Abstract: Objective: To compare coronary risk factors and disease prevalence among Indians, Pakistanis, and Bangladeshis, and in all South Asians (these three groups together) with Europeans. Design: Cross sectional survey. Setting: Newcastle upon Tyne. Participants: 259 Indian, 305 Pakistani, 120 Bangladeshi, and 825 European men and women aged 25-74 years. Main outcome measures: Social and economic circumstances, lifestyle, self reported symptoms and diseases, blood pressure, electrocardiogram, and anthropometric, haematological, and biochemical measurements. Results: There were differences in social and economic circumstances, lifestyles, anthropometric measures and disease both between Indians, Pakistanis, and Bangladeshis and between all South Asians and Europeans. Bangladeshis and Pakistanis were the poorest groups. For most risk factors, the Bangladeshis (particularly men) fared the worst: smoking was most common (57%) in that group, and Bangladeshis had the highest concentrations of triglycerides (2.04 mmol/l) and fasting blood glucose (6.6 mmol/l) and the lowest concentration of high density lipoprotein cholesterol (0.97 mmol/l). Blood pressure, however, was lowest in Bangladeshis. Bangladeshis were the shortest (men 164 cm tall v 170 cm for Indians and 174 cm for Europeans). A higher proportion of Pakistani and Bangladeshi men had diabetes (22.4% and 26.6% respectively) than Indians (15.2%). Comparisons of all South Asians with Europeans hid some important differences, but South Asians were still disadvantaged in a wide range of risk factors Findings in women were similar. Conclusion: Risk of coronary heart disease is not uniform among South Asians, and there are important differences between Indians, Pakistanis, and Bangladeshis for many coronary risk factors. The belief that, except for insulin resistance, South Asians have lower levels of coronary risk factors than Europeans is incorrect, and may have arisen from combining ethnic subgroups and examining a narrow range of factors.